2013
DOI: 10.1128/aem.02079-13
|View full text |Cite
|
Sign up to set email alerts
|

Snf1 Is a Regulator of Lipid Accumulation in Yarrowia lipolytica

Abstract: In the oleaginous yeast Yarrowia lipolytica, de novo lipid synthesis and accumulation are induced under conditions of nitrogen limitation (or a high carbon-to-nitrogen ratio). The regulatory pathway responsible for this induction has not been identified. Here we report that the SNF1 pathway plays a key role in the transition from the growth phase to the oleaginous phase in Y. lipolytica. Strains with a Y. lipolytica snf1 (Ylsnf1) deletion accumulated fatty acids constitutively at levels up to 2.6-fold higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 54 publications
6
94
2
2
Order By: Relevance
“…SNF2 deletion has been found to enhance lipid accumulation [76]. Inactivation of the SNF1 gene led to an enhanced constitutive fatty acid accumulation and citric acid production in Y. lipolytica [66,77]. An alternative strategy to enhance carbon flux re-direction from citric acid production to fatty acid biosynthesis is to overexpress ACC1 or use hyperactive Acc1p [67,78].…”
Section: Discussionmentioning
confidence: 99%
“…SNF2 deletion has been found to enhance lipid accumulation [76]. Inactivation of the SNF1 gene led to an enhanced constitutive fatty acid accumulation and citric acid production in Y. lipolytica [66,77]. An alternative strategy to enhance carbon flux re-direction from citric acid production to fatty acid biosynthesis is to overexpress ACC1 or use hyperactive Acc1p [67,78].…”
Section: Discussionmentioning
confidence: 99%
“…Engineering of the S. cerevisiae D5A strain for xylose utilization has been previously described (Hector et al, 2011), however, our strategy differed in that we targeted integration of our three-gene expression cassette to knock-out a negative regulator of a key pentose transporter (Gal2p) to ensure effective expression of this transporter in the presence of glucose. We then further engineered BFY692 for increased lipid accumulation by deleting the global regulator SNF1 as it has previously been shown to play an important role in lipid accumulation in both S. cerevisiae and Y. lipolytica (Chumnanpuen et al, 2012;Seip et al, 2013). This required a two-step process as D5A is a diploid yeast (Bailey et al, 1982).…”
Section: Engineering Of S Cerevisiae For Xylose Utilization and Incrmentioning
confidence: 99%
“…In S. cerevisiae, SNF1 encodes an ADP-activated serine/threonine kinase (Mayer et al, 2011) that, in addition to its role in regulating carbon homeostasis and general stress responses, regulates genes involved in lipid synthesis and nitrogen metabolism (Usaite et al, 2009;Chumnanpuen et al, 2012) and has been shown to regulate the first committed step of fatty acid synthesis by directly phosphorylating and thus inactivating acetyl-CoA carboxylase (Mitchelhill et al, 1994;Woods et al, 1994). Snf1 -mutants have also been shown to be defective in glycogen synthesis (Thompson-Jaeger et al, 1991; Hardie et al, 1998) and β-oxidation of lipids (Zaman et al, 2008;Usaite et al, 2009), and have shown up-regulation of genes involved in lipid biosynthesis particularly those leading to an increase in the acetyl-CoA pool and the downstream fatty acid synthases and glycerol-3-phosphate dehydrogenase that work in concert to turn that pool into neutral lipids (Seip et al, 2013). In addition, a SNF1 knock-out in the oleaginous yeast Yarrowia lipolytica showed increased fatty acid accumulation over that of wild type in both nitrogen replete and deplete conditions (Seip et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the maximum level of intracellular lipid accumulation in resting cells is usually achieved over several days (Seip et al, 2013), making this process time-consuming. Therefore, any attempt to enhance the growth and accumulation rate will result in a higher overall productivity.…”
Section: Challenges In Upgrading the Y Lipolytica Platformmentioning
confidence: 99%